Low pH reduces the activity of ceftolozane/tazobactam in human urine, but confirms current breakpoints for urinary tract infections. (3rd December 2019) - Nussbaumer-Pröll, Alina Karoline; Eberl, Sabine; Reiter, Birgit; Stimpfl, Thomas; Dorn, Christoph; Zeitlinger, Markus
Abstract: Background: Acidic pH has been shown to impact the antibiotic activity of non-β-lactams in urine. Objectives: To investigate the in vitro activity of ceftolozane/tazobactam compared with meropenem at different pH settings in urine. Methods: We determined the MICs for 30 clinical isolates of Escherichia coli, 25 clinical isolates of Klebsiella pneumoniae and 24 clinical isolates of Proteus mirabilis in pooled human urine and standard growth medium at pH 5 and 7. Time–kill curves were produced for one representative clinical isolate of tested bacterial strains in urine at pH 5, 6 and 7 for both antibiotics at concentrations above and below the MIC. HPLC analysis of the stability of ceftolozane/tazobactam and meropenem was performed at different pH values. Results: The median MICs of both antibiotics were up to 8-fold higher at pH 5 than at pH 7. Bacterial growth of E. coli was not impacted by pH, while for K. pneumoniae and P. mirabilis low pH slightly reduced growth. Compared with pH 7, pH 5 resulted in a significant decrease in antibiotic activity with a delta of up to 3 log10 bacterial counts after 24 h. Impact of acidic pH was lowest for P. mirabilis ; however, this strain metabolically increased the pH during experiments. Stability was not impacted by low pH. Conclusions: Acidic pH had a significant negative impact on the activity of ceftolozane/tazobactam and meropenem in urine. Considering concentrations achieved in urine, our results confirm existing breakpoints and do not advocate increasing ceftolozane/tazobactam breakpoints for urinary tract infections.